RISK FACTORS FOR THE DEVELOPMENT OF NON-COMMUNICABLE CHRONIC DISEASES IN THE ELDERLY (CIPEEX, 2025)
Objective: To identify risk factors for the development of non-communicable chronic diseases (NCDs) in the elderly. Method: This is an integrative review. Article searches were conducted in the databases National Library of Medicine and National Institutes of Health (PubMed), Virtual Health Library (BVS), and Google Scholar. Results: Female sex, sedentary behavior, diet quality, and body weight were risk factors for the occurrence of NCDs. Conclusion: It becomes imperative to identify risk factors for the occurrence of chronic diseases. This analysis is essential to provide support for professional practice and for generating information that can substantiate and improve health strategies in elderly support centers.
Keywords: chronic disease; risk factors; aged; health of the elderly